ACTION-ORIENTED APPROACH IN FOREIGN LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Today, increasing communication among people from various countries of the world increase not only the need of foreign language learning but also the methods, approaches and techniques. In parallel with these needs, Common European Framework of Reference for Languages (C.E.F.R.) suggests Action-Oriented Approach where the learners are “social agents”1. Learners/users are responsible for their own learning in this approach where the social dimension is first mentioned in language teaching. The need to use the language that emerged while fulfilling the tasks makes learning process effective and the learner active. Action oriented approach considers the learner as a social agent in classroom where learning is a social learning environment and develops linguistic and pragmatic skills besides communicative skills